High Ionic Strength Formation of DOPA‐Melanin Coating for Loading and Release of Cationic Antimicrobial Compounds. Issue 6 (20th May 2014) - Kuang, Jinghao; Guo, Jason L.; Messersmith, Phillip B.
<x xml:space="preserve">Abstract</x> Conformal DOPA‐melanin films are formed on a variety of substrates by simple dip‐coating in an alkaline DOPA solution at high ionic strength. Compared to polydopamine, DOPA‐melanin coatings have the advantage of high hydrophilicity and also the ability to bind and release cations. The latter is demonstrated by using DOPA‐melanin coated polycarbonate to form an antibacterial surface that inhibits and kills S. aureus. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>